The role of single-cell RNA sequencing in cardiac tumour - a case report - Qi, Xian-Jie; Wei, Ting; Abba, Isah Amir; Zhang, Sheng-Qiang; Meng, Jin-jin; Shi, Chao; Jiang, Yiyao (Journal of the Pakistan Medical Association, 2023)
A 65-year-old woman presented to our hospital with 5 days of chest tightness, dyspnoea, and lower abdominal distension. Echocardiography revealed a mass in the right atrium. An emergency operation was carried out to prevent tumour shedding. The patient was discharged on the 4th day of tumour resection, without any complications At the 18 months follow-up, she suffered from kidney and lung tumours. She refused any treatment and passed away. scRNA-seq was applied to analyse the nature of the tumour. The cellular components of benign tumours include chondrocytes, smooth muscle cells, fibroblasts, mesenchymal stromal cells, and osteoblasts. Additionally, the cyclic guanosine monophosphate (cGMP-PKG) signalling pathway, transcriptional misregulation in cancer, and the p53 signalling pathway may be related to the growth of this tumour. scRNA-seq is a good approach to analyse growth patterns of cardiac tumours and helpful for distinguishing the nature of the tumour. Keywords: Sequence Analysis, RNA, Cardiac tumour.